The Artin Exponent of Projective Special Linear Group PSL (2, P‘) (Journal of the College of Basic Education, 2022)
This paper finds the Artin characters and Artin exponent dependingon the character table and conjugacy classes of projective special lineargroup PSL (2,P*).Then we prove that Artin exponent of PSL (2, P*) isequal to p*' where P is a prime number , p=3 and k> 0.